Assessing Measurement Quality of Multidimensional Classroom Incivility Scale in Higher Education - Asfiati, Asfiati; Cahyadi, Ani; Hendryadi, Hendryadi; Hartinah, Sitti (Frontiers in Education, 2022)
This study examined the reliability and validity of a measure of classroom incivility within an Indonesian context. Data were collected from 334 participants through two stages of online questionnaire distribution. The measurement quality was evaluated through seven stages of partial least squares confirmatory composite analysis (PLS-CCA). Our findings confirm the multidimensionality of classroom incivility (class disruption, disrespectful communication, integrity violation, and use of the cell phone). In addition, all sub-scales of classroom incivility were negatively related to civility and prosocial behavior, and no significant difference was found between male and female students. Higher education institutions in Indonesia can use this instrument as a supplementary tool to evaluate the level of classroom incivility. We also discuss its practical implications in educational settings in general and offer suggestions for future research on classroom incivility in non-Western countries.